Is the Stock Market Overvalued: A Study in the Context of Bangladesh? - Abdullah, Mohammad Nayeem; Parvez, Kamruddin; Khaled, Moslehuddin (Asian Business Review, 2012)
The primary objective of this paper is to analyze if the Market overvalued. We studied prices of 17 actively companies in the Market from 2006 to 2010 and used three Valuation Ratios with an explicit corporate sector along with overall market index data and found that the Stock Marke overvalued. The analysis was completed in two stages. At first we analyzed each of the 17 companies to determine the condition of each company .This part shows that among 17 companies most of the companies’ share prices are overvalued and they are also inefficient in managing costs. The second stage of the analysis is composed of 17 companies share prices along with examination of capital accumulation in corresponding period. This result also shows that the market overvalued. From my analysis a relationship has been found between mass capital accumulation and Market Overvalued.